The Distribution of Wealth in Sweden: Trends and Driving factors - N. Anders Klevmarken (Uppsala University, Department of Economics, 2006)
Reviewing trends in the Swedish distribution of wealth it is demonstrated that the baby-boom cohorts have become relatively wealthy, both in terms of private wealth and in claims on the pension system. Results from a simulation model suggest that the elderly in the future will no longer belong to the relatively poor. They will though become relatively vulnerable to swings in the financial markets because a large share of their wealth is in the form of financial assets.This paper also argues that private life-cycle savings have been relatively weak in Sweden, while most of these kind of savings have been done through the public and collective pension systems. We see, however, indications of increasing life-cycle savings.
urn:nbn:se:uu:diva-83068
Keywords: D31; 330; Distribution of wealth; portfolio composition; notional pension wealth; baby-boom cohorts; liabilities; financial assets; Vermögensverteilung; Portfolio-Management; Alte Menschen; Sparen; Gesetzliche Rentenversicherung; Schweden